Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2015)
In this issue of Nordic Journal of Working Life Studies, we present seven quite different articles, all authored by researchers from Sweden. Three of the articles examine some general trends in working life: The first article examines the precariousness of the labor market, and two articles examine how increasing global competition affects the quality of work in the service sector in the Nordic countries. Four articles focus on mechanisms that create inequality in working life and the labor market: Gender inequality in the working environment is examined in two articles. In one article, it is examined how ethnic inequality is maintained in work organizations. And one article examines how stigmas from certain organizations are transferred to the employees of the organization (...)